Design of a lookahead controller in heavy duty trucks - Abdallahi, Hodan Ahmed (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
The increase in oil prices and green house emissions requires immediate action to reduce fuel use on a worldwide scale. The largest consumer of such fuels is the transportation industry and within that industry Heavy Duty Vehicles (HDV) are the major consumers. The need arises for minimization of fuel consumption in HDV's in a manner simple enough to be used by the vehicle in open road missions. In this study, a lookahead control method was designed which adjusts longitudinal motion, signified by velocity of the vehicle system using knowledge of fluctuations in road grade. Another lookdown controller was also designed which used only instantaneous road grade in addition to instantaneous velocity condition to generate efficient velocity trajectories. Through computer simulations on a vehicle of 40 tons a reduction in fuel consumption in the lookdown strategy was shown, however, larger reductions were achieved by the lookahead controller. Therefore, the utilization of road information in vehicle control presents a promise of reduction in economic cost as well as environmental impact for heavy duty vehicles.